Pengaruh Konsep Diri Terhadap Kesehatan Mental di Kecamatan Sukaraja - Marlena, Hesni; Nabila, Wika; Resitawati, Siana (Yayasan Darussalam Bengkulu, 2022)
This research aims to test whether there is an influence of self-concept on mental health in adolescents in Sukaraja Seluma sub-district. This research uses a quantitative method, the data collection technique is by distributing a questionnaire with 20 items and collecting data from 128 respondents. This research was analyzed using quantitative analysis SPSS 26 by testing regression, correlation, normality test, reliability test and R square. Based on the results of this study, it shows that the influence of self-concept on the mental health of adolescents in Sukaraja Seluma sub-district is in the weak category at 29.2%.